Pengembangan Usaha Mikro Kecil Menengah (UMKM) di Destinasi Wisata Pantai Topejawa Kabupaten Takalar Pasca Covid 19 - Daniel Adolf Ohyver; Agus Syam; Muhammad Jufri; Muhammad Alfa Sikar (Politeknik Pariwisata Makassar, 2023)
The coronavirus (COVID-19) outbreak is increasingly spreading and spreading rapidly and is becoming the biggest global polemic for now. It also affects limited SME activity and fewer direct-to-consumer purchases than usual. The development of MSMEs in Topejawa Beach Tourist Destinations, Takalar Regency in the Recovery of the Covid-19 Pandemic, in addition to requiring strategies that can affect the Development of MSMEs in Topejawa Beach Tourist Destinations, Takalar Regency, is a marketing strategy. Based on the background description above, the researcher is interested in conducting research and compiling a thesis, with the title